The crisis of the señorial society and the status malaise of the elites in Chile - Danilo Martuccelli (Íconos)
Taking Chilean society as a case study, this article is inserted in discussions on political power and economic elites, drawing attention to the importance of status. The objective is to propose an interpretation of the specificity of this crisis and of elite malaise in Chile today. To this end, an argument is presented based on the principles of interpretative historical sociology from Max Weber’s theory of stratification (the distinction between classes, status, and party) and the methodology of ideal types. On this basis, an analytical reasoning is presented in three moments – the first marked by the validity of the ideal type of señorial society; the second, by its crisis in the 1970s and by the recomposition of the elite domain after the coup d'état, when there was a successful restructuring of classes and parties and an insufficient status restoration; and the third moment characterized by the specificity of the current malaise of the elites in Chile which, unlike other political or economic crises, has its focus on the status order. Thus, attention is drawn to the need to complement the study of the relations between economic elites and political power, differentiating between legitimacy crises and status malaise.